Infant stimulation reduces weight loss and increases breastfeeding: a randomized controlled trial - Vesga Gualdrón, Lucy Marcela; Durán de Villalobos, María Mercedes; Bernal Camargo, Nancy Milena (Investigación y Educación en Enfermería, 2023)
Objective. The study aimed to measure the effect of auditory, tactile, visual, and vestibular (ATVV) stimulation therapy on sucking effectiveness (SE), infant-feeding mode, weight, height, and head circumference (HC) of full-term infants. Methods. A single-blinded randomized trial with a sample of 107 mother-child dyads. Inclusion criteria were healthy first-time mothers and full-term infants with no known pathological conditions, weighing between 2500 and 4000 grams, and recommendation of exclusive or predominant breastfeeding. The mothers in the experimental group (EG) received training in ATVV stimulation therapy and provided it from birth (first 24 hours of life) until the end of the follow-ups at week 5. The control group (CG) received only standard care that included education on warning signs and basic guidance on breastfeeding. SE, infant-feeding mode, and neonatal growth were measured at weeks 2 and 5. Results. In contrast to CG infants, the EG infants drank 2.02 cc more human milk in one minute of effective breastfeeding (p=0.002) at week 2 and 5.51 cc more at week 5 (p<0.0001). They showed greater adherence to breastfeeding at week 5 (p=0.025) and gained more weight: 8.35 grams/day (p=0.009) and 4.19 grams/day (p=0.008). HC did not differ between groups, and height difference was statistically significant at week 5 (p=0.025). Conclusion. ATVV stimulation therapy has a positive effect on neonatal health as it promotes effective sucking and exclusive breastfeeding, reduces weight loss, and improves neonatal growth.